Anxiolytic Properties of Valeriana officinalis in the Zebrafish: A Possible Role for Metabotropic Glutamate Receptors - Del Valle-Mojica, Lisa M.; Ortíz, José G. (Planta Medica, 2012)
Valerian extract is used in complementary and alternative medicine for its anxiolytic and sedative properties. Our previous research demonstrated valerian interactions with glutamate receptors. The purpose of this study was to determine if valerian anxiolytic properties are mediated by metabotropic glutamate receptors (mGluR) such as mGluR (1/5) (mGluR I) and mGluR (2/3) (mGluR II). Adult wild-type zebrafish (Danio rerio) prefer the black compartment and avoid the white compartment in the dark/light preference task. Zebrafish exposed to 1 mg/mL of valerian extract or 0.00117 mg/mL valerenic acid increased their residence time in the white side by 84.61 ± 6.55 % and 58.30 ± 8.97 %, respectively. LAP3 (mGluR I antagonist) and EGLU (mGluR II antagonist) significantly inhibited the effects of valerian and valerenic acid. These results demonstrated that valerian and valerenic acid have anxiolytic properties in the zebrafish. Moreover, the selective interaction of valerian with mGluR I and II represent an alternative explanation for the anxiolytic properties of this plant and support the role of mGluR in anxiety.
Keywords: zebrafish; Danio rerio; Valeriana officinalis; Valerianaceae; anxiety; valerenic acid; scototaxis